Coronary spasm secondary to cefuroxime injection, complicated with cardiogenic shock – a manifestation of Kounis syndrome: case report and literature review. Issue 7 (October 2018) - Mitsis, Andreas; Christodoulou, Evi; Georgiou, Panayiota
Kounis syndrome is defined as the coincidental occurrence of an acute coronary syndrome with hypersensitivity reactions following an allergic event. The three reported variants of Kounis syndrome are vasospastic allergic angina, allergic myocardial infarction and stent thrombosis with occluding thrombus. The syndrome is caused by various inflammatory mediators. The pathophysiological characteristics of Kounis syndrome involve coronary artery spasm and/or atheromatous plaque erosion or rupture during an allergic reaction. Several causes have been described to induce Kounis syndrome, and their number is increasing rapidly. The haemodynamic effect of the syndrome complicated by cardiogenic shock seems to combine allergic shock with extensive peripheral vasodilation and myocardial suppression with the characteristics of cardiogenic shock. Treatment of Kounis syndrome is challenging because it needs management of both cardiac and allergic manifestation simultaneously. We present a case report of type I Kounis syndrome, with coronary spasm secondary to cefuroxime injection complicated with cardiogenic shock. A brief review of the literature on the various facets of this condition is also provided.